Bioprocess considerations for microalgal-based wastewater treatment and biomass production. (February 2015) - Zeng, Xianhai; Guo, Xiaoyi; Su, Gaomin; Danquah, Michael K.; Zhang, Shiduo; Lu, Yinghua; Sun, Yong; Lin, Lu
Abstract: Nowadays, microalgae received wide attention due to several advantages for biochemicals and renewable/sustainable biofuels production. Moreover, the utilization of microalgae as robust cellular species for biological nutrient removal from industrial and domestic wastewater streams has been of great research interest amongst the several biotechnological applications of microalgae. This is due to the capacity for effective photosynthetic uptake of high concentrations of minerals, ionogens, and organics by microalgae whilst simultaneously biosequestering carbon dioxide. This review discusses the utilization of microalgae for wastewater nutrients removal. It discusses the bioprocess potentials and challenges of using microalgal cells for full-scale microbial wastewater treatment under free and immobilized conditions. It also presents a mechanistic insight of the mass transfer processes essential for optimal uptake of nutrients during photobioreaction. A new bioprocess paradigm based on integrated upstream and downstream processes for multi-purpose microalgae bioprocessing and bioresource generation is discussed.